Sink trap: duckweed and dye attractant reduce mosquito populations. Issue 1 (22nd October 2019) - Cuthbert, Ross N.; Coughlan, Neil E.; Dick, Jaimie T. A.; Callaghan, Amanda
Abstract: Duckweeds, such as Lemna minor Linnaeus (Alismatales: Lemnaceae), are common in aquatic habitats and have been suggested to reduce larval mosquito survivorship via mechanical and chemical effects. Furthermore, pond dyes are used increasingly in aquatic habitats to enhance their aesthetics, although they have been shown to attract mosquito oviposition. The present study examined the coupled effects of L. minor and black pond dye on the oviposition selectivity of Culex pipiens Linnaeus (Diptera: Culicidae) mosquitoes in a series of laboratory choice tests. Subsequently, using outdoor mesocosms, the combined influence of duckweed and pond dye on mosquito abundances in aquatic habitats was quantified. Mosquitoes were strongly attracted to duckweed, and oviposited significantly greater numbers of egg rafts in duckweed‐treated water compared with untreated controls, even when the duckweed was ground. The presence of pond dye interacted with the duckweed and further enhanced positive selectivity towards duckweed‐treated water. The presence of duckweed caused significant and sustained reductions in larval mosquito numbers, whereas the relative effects of dye were not evident. The use of floating aquatic plants such as duckweed, combined with dye, may help reduce mosquito populations via the establishment of population sinks, characterized by high rates of oviposition coupled with high levels of larval mortality. Abstract : Oviposition by adult Culex pipiens mosquitoes is significantly increased towards aquatic habitats treated with duckweed and black pond dye. Duckweed and black pond dye act in synergy to increase positive selection by mosquitoes towards treated habitats. Duckweed drives significant and sustained reductions of larval mosquito abundances in field‐based mesocosms, offering a potential population sink effect.